Removal of a Subset of Non-essential Genes Fully Attenuates a Highly Virulent Mycoplasma Strain - Jores, Joerg; Ma, Li; Ssajjakambwe, Paul; Schieck, Elise; Liljander, Anne; Chandran, Suchismita; Stoffel, Michael H.; Cippa, Valentina; Arfi, Yonathan; Assad-Garcia, Nacyra; Falquet, Laurent; Sirand-Pugnet, Pascal; et al. (Frontiers in Microbiology, 2019)
Mycoplasmas are the smallest free-living organisms and cause a number of economically important diseases affecting humans, animals, insects and plants. Here, we demonstrate that highly virulent Mycoplasma mycoides subspecies capri (Mmc) can be fully attenuated via targeted deletion of non-essential genes encoding, among others, potential virulence traits. Five genomic regions, representing approximately ten percent of the original Mmc genome, were successively deleted using Saccharomyces cerevisiae as an engineering platform. Specifically, a total of 68 genes out of the 432 genes verified to be individually nonessential in the JCVI-Syn3.0 minimal cell, were excised from the genome. In vitro characterization showed that this mutant was similar to its parental strain in terms of its doubling time, even though ten percent of the genome content were removed. A novel in vivo challenge model in goats revealed that the wild-type parental strain caused marked necrotizing inflammation at the site of inoculation, septicemia and all animals reaching endpoint criteria within seven days after experimental infection. This is in contrast to the mutant strain, which caused no clinical signs nor pathomorphological lesions. These results highlight, for the first time, the rational design, construction and complete attenuation of a Mycoplasma strain via synthetic genomics tools. Trait addition using the yeast-based genome engineering platform and subsequent in vitro or in vivo trials employing the Mycoplasma chassis will allow us to dissect the role of individual candidate Mycoplasma virulence factors and lead the way for the development of an attenuated designer vaccine.